A coproduced patient and public event: An approach to developing and prioritizing ambulance performance measures. (25th August 2017) - Irving, Andy; Turner, Janette; Marsh, Maggie; Broadway‐Parkinson, Andrea; Fall, Dan; Coster, Joanne; Siriwardena, A. Niroshan
Abstract: Background: Patient and public involvement (PPI) is recognized as an important component of high‐quality health services research. PPI is integral to the Pre‐hospital Outcomes for Evidence Based Evaluation (PhOEBE) programme. The PPI event described in detail in this article focusses on the process of involving patients and public representatives in identifying, prioritizing and refining a set of outcome measures that can be used to support ambulance service performance measurement. Objective: To obtain public feedback on little known, complex aspects of ambulance service performance measurement. Design: The event was codesigned and coproduced with the PhOEBE PPI reference group and PhOEBE research team. The event consisted of brief researcher‐led presentations, group discussions facilitated by the PPI reference group members and electronic voting. Setting and participants: Data were collected from eighteen patient and public representatives who attended an event venue in Yorkshire. Results: The results of the PPI event showed that this interactive format and mode of delivery was an effective method to obtain public feedback and produced a clear indication of which ambulance performance measures were most highly favoured by event participants. Discussion and conclusions: The event highlighted valuable contributions the PPI reference group made to the design process, supporting participant recruitment and facilitation of group discussions. In addition, the positive team working experience of the event proved a catalyst for further improvements in PPI within the PhOEBE project.